Analisis Pengakuan Pendapatan Dan Pembebanan Biaya Kontrak Konstruksi Menurut PSAK No. 72 Pada Perusahaan Jasa Konstruksi (Studi Pada Cv. Wanamartha Anugerah Samawa) - Ayu, Nurmaya Ade Kresna; Mariadi, Yusli (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
The decision-makingg made by the company is reflected from the resulting of financial statements. However, there are several companies that complete financial statements only for tax reporting needs, so they do not fo through the auditing process by expert and the report cannot be confirmed whether it is in accordance with the applicable accounting standards, especially in revenue recognition and cost charging, which are two important components of a company’s profit or loss generator. The purpose is ti describe how the analysis of revenue recognition and cost charging according to the Financial Accounting Standards Statement (PSAK) No. 72 in construction service companies CV. Wanamartha Anugerah. This research is qualitative descriptive and data collectiong techniques are interview and documentation. The result is that revenue recognition of CV. Wanamartha has been in accordance with PSAK 72 but the cost charging on the CV. Wanamartha is not in accordance with PSAK 72.